PEMBELAJARAN RAGAM GERAK PERANGAN DALAM TARI RENGGAMATAYA PUTRI BERBASIS METODE IMITASI DAN DRILL: STUDI KASUS DI YAYASAN PAMULANGAN BEKSA SASMINTA MARDAWA YOGYAKARTA - Prabandari, Dyah Ajeng; Kusumastuti, Eny (Penerbit Lafadz Jaya, 2025)
This study discusses the learning process of various war movements in Renggamataya Putri Dance as applied at the Pamulangan Beksa Sasminta Mardawa Foundation in Yogyakarta. The main issue in this study is how the imitation and drill methods applied by teachers in delivering various war movements, material to adult female elementary school students, particularly in the context of classical Yogyakarta-style dance, which requires perseverance, precision, and mastery of advanced techniques. The objective of this study is to understand and describe the implementation of the learning process of War Movement Variations based on imitation and drill methods, as well as determining the effectiveness of these methods on the development of students' skills. This study employs qualitative research design with a case study approach, utilizing data collection techniques such as observation, interviews, and documentation. The results of the study indicate that the learning process using imitation and drill methods consistently improves students' ability to memorize movements, improve technique, and build a deep understanding of the variety of war movements. In each session, the teacher provides direct examples of movements, repeats them using counting or accompaniment, and corrects students' mistakes on an. The final evaluation showed that most students were able to perform the dance well based on the aspects of wiraga, wirama, and wirasa. The conclusion of this study is that the imitation and drill methods are effective in building the foundation of classical dance skills in elementary school students, especially in the gradual mastery of various war movements.